THE EFFECT OF INVESTMENT DECISION AND FUNDING DECISION ON FIRM VALUE IN COMPANIES AUTOMOTIVE LISTED ON THE INDONESIA STOCK EXCHANGE 2015-2019 PERIOD - Sucitra Dewi; Thezar Fiqih Hidayat Hasibuan (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
This study aims to examine the effect of Investment Decisions, Funding Decisions, Dividend Policy and Intellectual Capital on Company Value in automotive companies listed on the Indonesia Stock Exchange in the 2015-2019 period. This research is a quantitative research with a descriptive approach. The population in this study are all automotive companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The sampling technique in this study used a saturated sampling technique (census), which is a sampling technique where the total population is used as the sample. The results of this study are based on the partial t-test results. Investment decisions have no effect on firm value and funding decisions have an effect on firm value and dividend policy has no effect on firm value.